(3GdhLjR aj Mbhb GdedcjI GdUfGYjI h GdJLGQjI (B:s (3efXeI GdJLGQI GdYGdejI, GJaGbjI JQHS, HQGAGJ GdGNJQGY, GdYdGeGJ GdJLGQjI, Mbhb GdedcjI GdUfGYjI h GdJLGQjI GdGNQi (B/s - (3GdNTQhe, YHO Gddg MSjfs ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2008)
(3ebOeI(B-(3GdaUd GdJegjOj (B: (3GdeHMK GdChd (B: (3Mbhb GdedcjI GdUfGYjI hGdJLGQjI hGdeJLQ (B: (3GdeHMK GdKGfj (B: (3GdWHjYI GdbGfhfjI dMbhb GdedcjI GdUfGYjI hGdJLGQjI (B: (3GdeHMK GdKGdK (B: (3deMI JGQjNjI Yf Mbhb GdedcjI GdUfGYjI hGdJLGQjI (B: (3GdeHMK GdQGHY (B: (3eUGOQ Mbhb GdedcjI GdUfGYjI hGdJLGQjI(B-(3GdaUd GdChd (B: (3GdJYQja HGJaGbjI GdLhGfH GdeJUdI HGdJLGQI ef Mbhb GdedcjI GdacQjI (B/ (3GJaGbjI JQHS (B(TRIPS) : (3GdeHMK GdChd (B: (3GdJYQja HefXeI GdJLGQjI GdYGdejI (B(W.T.O) : (3GdeHMK GdKGfj (B: (3GdMbhb GdJj JYGdLgG GJaGbjI JQHS (B(TRIPS) : (3GdeHMK GdKGdK (B: (3CMcGe GfaGP Mbhb GdedcjI GdUfGYjI hGdJLGQjI hab GJaGbjI JQHS (B: (3GdeHMK GdQGHY (B: (3CKQ GfVeGe GdCQOf defXeI GdJLGQI GdYGdejI hNGUI GJaGbjI (B(TRIPS) (3ai GdGbJUGO GdCQOfj(B-(3GdaUd GdKGfj (B: (3HQGAGJ GdGNJQGY (B(Patents) : (3GdeHMK GdChd (B: (3JYQja HQGAI GdGNJQGY hCgejI MeGjJgG (B: (3GdeHMK GdKGfj (B: (3TQhW efM HQGAI GdGNJQGY (B: (3GdeHMK GdKGdK (B: (3GdHQGAI (B: (3GdeHMK GdQGHY (B: (3Mbhb hGdJRGeGJ eGdc HQGAI GdGNJQGY (B: (3GdeHMK GdNGeS (B: (3GdJQGNjU GdGLHGQjI GdGLHGQjI aj HQGAGJ GdGNJQGY (B: (3GdeHMK GdSGOS (B: (3GdMeGjI GdbGfhfjI dHQGAGJ GdGNJQGY (B: (3GdeHMK GdSGHY (B: (3GfbVGA HQGAI GdGNJQGY hHWdGfgG(B-(3GdaUd GdKGdK (B: (3GdYdGeGJ GdJLGQjI (BTrademarks : (3GdeHMK GdChd (B: (3JYQja GdYdGeI GdJLGQjI (B: (3GdeHMK GdKGfj (B: (3CgejI GdYdGeI GdJLGQjI hhXGFagG (B: (3GdeHMK GdKGdK (B: (3CTcGd GdYdGeI GdJLGQjI (B: (3GdeHMK GdQGHY (B: (3TQhW GdYdGeI GdJLGQjI (B: (3GdeHMK GdNGeS (B: (3Mbhb eGdc GdYdGeI GdJLGQjI (B: (3GdeHMK GdSGOS (B: (3GdMeGjI GdeOfjI ddYdGeI GdJLGQjI (B: (3GdeHMK GdSGHY (B: (3GdMeGjI GdLRGFjI ddYdGeI GdJLGQjI (B: (3GdeHMK GdKGef (B: (3GfbVGA GdMb aj GdYdGeI GdJLGQjI(B-(3GdaUd GdQGHY (B: (3Mbhb GdedcjI GdUfGYjI hGdJLGQjI GdCNQi (B: (3GdeHMK GdChd (B: (3bGfhf GdQShe GdUfGYjI hGdfeGPL GdUfGYjI (B: (3GdeHMK GdKGfj (B: (3bGfhf GdHjGfGJ GdLZQGajI GdCQOfj (B: (3GdeHMK GdKGdK (B: (3bGfhf MeGjI GdJUeGje ddOhGFQ GdeJcGedI GdCQOfj (B: (3GdeHMK GdQGHY (B: (3bGfhf GdefGaSI ZjQ GdeTQhYI hGdCSQGQ GdJLGQjI (B: (3GdeHMK GdNGeS (B: (3bGfhf MeGjI GdCUfGa GdfHGJjI(B.s
(3GdedGMb U(B.239 (3HHdjhZQGajG(B: (3U(B.391 s
Keywords: (3GdedcjI GdUfGYjIs; (3GdefXeGJ GdJLGQjIs; (3HQGAGJ GdGNJQGYs